An analytical approach for pull-out behavior of TRM-strengthened rammed earth elements - Romanazzi, Antonio (2022)
Rammed earth constructions, beyond being largely spread in the built heritage, are known for their high seismic vulnerability, which results from high self-weight, lack of box behavior and low mechanical properties of the material. Hence, to mitigate this seismic vulnerability, a compatible textile reinforced mortar (TRM) is here proposed as a strengthening solution, because of its reduced mass and high ductility. The few research about the structural behavior of TRM-strengthened rammed earth elements addresses the global behavior, overlooking the local behavior of the system. An analytical approach to infer the bond stress-slip relationship following the direct boundary problem is proposed. Based on a previous series of pull-out tests, an adhesion-friction constitutive law is portrayed considering also a damage model that considers the degradation of the reinforcing fibers due to friction.